Analisis Teknologi dan Permasalahan pada Pembelajaran Jarak Jauh dimasa Pandemi Covid-19 pada Siswa SMK (Studi Kasus: Siswa Kelas XII Jurusan Teknik Pemesinan SMKN 1 Jenangan) - Humam Huwaidi Al-Marzuq; Diah Priharsari; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The point of view of students regarding blended learning carried out during the COVID-19 pandemic took place at SMKN 1 Jenangan. Blended learning is something that must be done by vocational students considering that they need practice while still paying attention to health protocols during the pandemic, so that there are online classes that they do. Blended learning is carried out only on certain subjects, such as productive subjects. Respondents in semi-structured interviews involved 8 students of the Mechanical Engineering Department of SMKN 1 Jenangan. The number of respondents in this study is adjusted to the data needs for research. The interview process was conducted by the researcher by recording and having obtained permission from each research respondent. The time used for each respondent is 8-15 minutes. After the semi-structured interview was completed, the researcher provided additional methods, namely observation. Observations were made to validate the data generated from the previous semi-structured interviews. After the two methods were completed, the researcher conducted an analysis using the thematic coding analysis method using the Atlas.ti 9 tool and the thematic coding results obtained 5 main themes and 39 secondary themes. The five main themes are as follows: (1) Online Learning, (2) Offline Learning, (3) Use of Technology, (4) Learning Constraints, (5) Learning Suggestions and Expectations. In the 5 codes, there are 39 secondary themes that explain the blended learning process, the use of technology during the blended learning process, the obstacles experienced during the blended learning process, and suggestions and expectations of the blended learning process from the student's perspective.